Effect of carbohydrate intake during wrestling practice on upper-body work in adolescents - Horswill, C. A.; Curby, D. G.; Bartoli, W.; Stofan, J. R.; Murray, R. (Pediatric Exercise Science, 2006)
We examined whether the type of fluid ingested during wrestling training would affect arm ergometry in adolescent athletes. Wrestlers (n = 11) trained for 2-hr sessions and consumed fluid containing 6% carbohydrate or a placebo of equal volume administered double blind and in randomized fashion. To account for training demands across beverage comparisons, energy expenditure (EE) was estimated by using the rate of appearance of CO2 (RaCO2) after 13C-bicarbonate ingestion. The performance test was completed after training and consisted of 6 min of intermittent, high-intensity arm cranking. The results showed the difference in total arm work (kg · m-2 · min) between carbohydrate (2,130 ± 263) and placebo (1,961 ± 401) conditions approached statistical significance (p = .07). Fluid intake matched 50% of sweat loss, resulting in modest dehydration for both treatments. Carbohydrate ingestion during training may enhance high-intensity intermittent arm work in adolescent wrestlers; however, the additive effects of carbohydrate dose and fluid volume for hydration need to be teased apart in subsequent research on adolescents performing such exercise.